‘The past is prologue to the future’: an introspective view of hospitality and tourism research - Theocharous, Antonis L.; Constanti, Panayiotis; Zopiatis, Anastasios (My University, 2015)
Since the early 1970s, scholars have contributed their talent and intellect towards the establishment of the discipline and the education of the next generation of hospitality and tourism professionals. Espousing the popular notion ‘‘publish or perish’’, numerous scholars have explored the discipline’s research foundations from an array of different perspectives, such as the ranking and rating of scholars, journal publications and institutions. This novel empirical endeavor aims to enrich the existing intellectual capital by investigating the publication strategies of forty-four prolific hospitality and tourism scholars, by focusing on three distinctive thematic areas, namely, a journal’s impact factor and citations, authorship specifics, and research themes. Findings are of interest to both current and future scholars in their quest for academic excellence and contributions, which further enhance the hospitality and tourism discipline.
Keywords: Bibliometrics; Publication strategies; Correspondence analysis; Linear mixed effects models (LMEM); Hierarchical clustering on principal component (HCPC)